Pemanfaatan Kunyit (Curcuma domestica Val) Untuk Memurnikan Minyak Jelantah - Muhammad Silmi Hi Abubakar; Siti Nuryanti; Suherman Suherman (Universitas Tadulako, 2018)
Study on the purification and quality test of used cooking oil with turmeric has been done. This study aims to determine the quality of cooking oil after purified turmeric. The quality parameters of oil studied were the moisture content, free fatty acids (FFA), and peroxide. The methods used for determination of these parameters were gravimetry for moisture content, acid-base titration for free fatty acids, and iodometric for peroxide. The test results for water from 0.6% to 0.4% free fatty acid from 1.2% to 0.2%, and peroxide levels before and after purification were successively from and 6 meq/g to 4 meq/g, respectively. Only free fatty acids of all three parameters met the requirement of SNI.